Magnetic skyrmions: from fundamental to applications. (22nd September 2016) - Finocchio, Giovanni; Büttner, Felix; Tomasello, Riccardo; Carpentieri, Mario; Kläui, Mathias
Abstract: In this topical review, we will discuss recent advances in the field of skyrmionics (fundamental and applied aspects) mainly focusing on skyrmions that can be realized in thin film structures where an ultrathin ferromagnetic layer (<1 nm) is coupled to materials with large spin–orbit coupling. We review the basic topological nature of the skyrmion spin structure that can entail a stabilization due to the chiral exchange interaction present in many multilayer systems with structural inversion asymmetry. The static spin structures and the dynamics of the skyrmions are also discussed. In particular, we show that skyrmions can be displaced with high reliability and efficiency as needed for the use in devices. We discuss major possible applications, such as memory, microwave oscillators and logic, and combinations of these, making skyrmions very promising candidates for future low power IT devices.